2004
DOI: 10.1038/sj.bdj.4811390
|View full text |Cite
|
Sign up to set email alerts
|

Marginal adaptation of three-unit fixed partial dentures constructed from pressed ceramic systems

Abstract: Purpose This study compares the marginal accuracy of posterior metal ceramic (MC), all-ceramic IPS Empress®2 and experimental pressed ceramic (EPC-VP 1989/4) three-unit fixed partial dentures (FPD), before and after luting and after thermo-mechanical fatigue in a dual-axis chewing simulator. Materials and methods Caries-free human teeth (n=160) were used as abutments for the fabrication of eighty posterior three-unit FPD, divided into two test-groups, IPS Empress®2 and EPC, of 32 samples each and one control g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
1
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 29 publications
(52 reference statements)
3
29
1
2
Order By: Relevance
“…IPS Empress2 presented the lowest values, around 63 μm [12,13,24] while the marginal misfit of ceramic restorations constructed with IPS Empress 2 and cemented with resin luting cement RelyX ARC showed satisfactory adaptation in this current study. The vertical misfit values of this study (Table 1) are in agreement with the data of previous studies, in accordance to the clinical acceptance [23,25]. At the Wolfart et al [23] study using SEM, the vertical misfits values were from 96 μm to 130 μm to completed crowns, differing with the lowest misfits values found at the present study (Table 1).…”
Section: Discussionsupporting
confidence: 92%
“…IPS Empress2 presented the lowest values, around 63 μm [12,13,24] while the marginal misfit of ceramic restorations constructed with IPS Empress 2 and cemented with resin luting cement RelyX ARC showed satisfactory adaptation in this current study. The vertical misfit values of this study (Table 1) are in agreement with the data of previous studies, in accordance to the clinical acceptance [23,25]. At the Wolfart et al [23] study using SEM, the vertical misfits values were from 96 μm to 130 μm to completed crowns, differing with the lowest misfits values found at the present study (Table 1).…”
Section: Discussionsupporting
confidence: 92%
“…28 The marginal fit values of experimental all-ceramic FPDs ranged between 89 µm and 130 µm in an in vivo study. 29 On the other hand, the findings of an in vitro study revealed mean marginal gap values of Empress 2 FPDs between 58 µm and 68 µm. 30 An explanation for these differences in the literature regarding marginal gaps in all-ceramic crowns might be attributed to many parameters, such as measurement methodology, measuring instruments used, the differences in material properties, sample size and the number of measurements per specimen.…”
Section: Discussionmentioning
confidence: 98%
“…Artificial aging was previously shown to influence the marginal integrity of all-ceramic FPDs 34. However, Att et al found no significant change in the marginal fit of zirconia FPDs after masticatory and thermal stimulation 29.…”
Section: Discussionmentioning
confidence: 99%